Outcome of Horizontal Strabismus Surgery and Factors Influencing Surgical Success - Parajuli, Rojeeta; Adhikari, Srijana; Poudel, Manish; Naluria, Hening; Oli, Radhika Upreti; Banjara, Pradeep; Thapa, Suman Shumsher (Nepalese Journal of Ophthalmology, 2024)
Introduction: Strabismus is a complex problem of eye alignment, binocularity, and cosmetics that affect vision and quality of life. Strabismus surgery helps to establish binocular fusion, expand the field of binocular vision, eliminate diplopia, correct a compensatory head posture, and improve cosmetic appearance. The outcomes of horizontal strabismus surgery range from 56.3-86.5%. It depends on different factors such as the type of strabismus, accurate measurement of pre-operative deviation, age at which strabismus surgery was performed for the first time, type of strabismus surgery, postoperative alignment, and binocularity. Regrettably, there is insufficient data regarding the prevalence of strabismus and the outcomes of surgical interventions in Nepal. This study addresses the outcome of strabismus surgery and the factors influencing surgical success conducted at a tertiary hospital.Objective: To evaluate the outcome of horizontal strabismus surgery and factors influencing surgical success.Methodology: The medical records of 206 patients who had undergone their first horizontal strabismus surgery at Tilganga Institute of Ophthalmology (TIO) from 2017 to 2020 were reviewed retrospectively. Those who completed a follow-up period for at least 3 months were included. Patients with restrictive, paralytic, and vertical strabismus were excluded from the study. The success of the surgery was defined by achieving an eye deviation of less than 10 prism diopters (PD) six weeks post-surgery. The influencing factors for surgical success (diagnosis, age group, visual acuity, binocular function, and pre-operative angle of deviations) were analyzed.Result: Complete data of 194 patients with follow-up periods of 6 weeks to 3 months were retrieved from the electronic medical record. The majority 116(59.8%) of the patients were between 6-18 years >18-53years 40.2% (78) with male to female ratio of 0.96:1. Majority of the participants had exotropia 124(63.9%) and mean pre-operative angle of deviation was 48.9±14.7PD (Range 10- 90). A good motor alignment (total success rate) was 44.3 %( 86); the success rate for esotropia was 36(41.9%) and for exotropia was 50(58.1%). Both fusion and stereopsis were significantly improved after surgery (P